A Review on the Most Important Medicinal Plants Effective in Cardiac Ischemia-Reperfusion Injury - Sedighi, Mehrnoosh; Sewell, Robert D. E.; Nazari, Afshin; Abbaszadeh, Saber; Cheraghi, Mostafa; Amini, Abdolhakim; Heydari, Zahra; Rafieian-Kopaei, Mahmoud (Current Pharmaceutical Design, 2019)
Ischemia, referring to reduction and restriction of perfusion to myocardial tissue which involves coronary artery through the formation of misplaced clots and thrombosis, is one of the most important cardiovascular diseases. Plant-based compounds help to improve or prevent disease by affecting the factors involved in the disease. This review was conducted to report the medicinal plants and factors effective in cardiac ischemiareperfusion (I/R) injury to supplement the knowledge about this disease and its prevention and treatment using certain medicinal plants and their active compounds. For this purpose, medicinal plants and their potential antioxidant activities, effects on lipid levels and plaque formation, atherosclerosis and development of cardiovascular diseases and ischemia were reviewed. Methods: To conduct this review, relevant articles published between 1983 and 2018 were retrieved from the Google Scholar, PubMed, Scientific Information Database, Web of Science, and Scopus using search terms antioxidant, ischemia, reperfusion, heart, infarct, inflammation, cholesterol and medicinal plants. Then, the eligible articles were reviewed. Results: The active compounds of plants, including phenolic compounds, flavonoids, and antioxidant compounds, can be effective on certain pathogenic factors particularly in decreasing cholesterol and blood pressure, preventing an increase in free radicals and ultimately reducing blood clots and vascular resistance to reduce and prevent ischemic disease and its harmful effects. Conclusion: Medicinal plants discussed in this article seem to be able to prevent cardiac damage and the disease progression via affecting the factors that are involved in ischemia.
Keywords: medicinal plants